OBESITY TO THE LUNG - FORCE VITAL CAPASITY (FVC) RELATION AT THE STUDENTS OF SMA NEGERI 2 BANDAR LAMPUNG - Dwika, Dicky Aditya; Berawi, Khairunissa; Susianti, Susianti; Muhartono, Muhartono (Majority, 2015)
Obesity or too-fat is an over relative human weight condition caused by accumulation of nutrition, especially carbohydrate and fat. Based on WHO data in 2006, there was 1.6 billion adult people in the world was in overweight condition and unless than 400 millions from that was in obesity condition. In Indonesia, based on Basic Health Research (Riskesdas) data in 2007, national prevalence in general obesity at >15 years old inhabitants was 10.3% (13.9% male, 23.8% female). Obesity, especially central obesity (abdominal) is associated with many metabolism disruption and illness. Besides that, obesity (especially morbid type) is also associated with many types of human respiratory disruption. The aims of this research were to find if there’s “related” or “unrelated” condition between obesity and Lung–Force Vital Capacity (FVC) at the studens of SMA N 2 Bandar Lampung. The research type that used is analitic descriptive research with cross-sectional research program. Respondents are counted 92 male and female students, data was analyzed univariate and bivariate using chi-square exam. The result of this research showed that 6.52% respondents were in obese-BMI. The result of chi-square statistic exam shows p=0.076 (p<0.1) which means that there was different value between respondents with obese- BMI and respondents with nonobese-BMI. Keywords: obesity, BMI, forced vital capacity (fvc)